PENERAPAN MODEL TEORI FLORENCE NIGHTIANGEL DALAM ASUHAN KEPERAWATAN ANAK DENGAN PNEUMONIA - Sarah Rahmania; Irna Nursanti (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
The purpose of this study was to provide nursing care for children with pneumonia based on Florence Nightiangel's theory. This research method is a case study with a nursing care approach based on Florence Nightiangel's theory. Data collection was done by interview, observation, physical examination and documentation study. The instrument used is an assessment format based on Florence Nightiangel nursing theory. The results of the assessment were found to be shortness of breath, coughing and difficult sputum removal, mild chest wall retraction on the subcosta, pulmonary sound sounded rochi, tachypnea breathing pattern, respiratory frequency 38x/min, there were infiltrates in both lung fields, environmental conditions of the house opposite the farm, house windows and ventilation are rarely opened so it is difficult to get fresh air and lighting from sunlight. There are two nursing problems, namely ineffective airway clearance, and ineffective family health management. The interventions carried out are based on SLKI and SIKI. After three days of nursing care, it was concluded that the top two nursing problems were partially solved. It is expected that nurses are able to provide and improve the quality of service in providing nursing care based on the Florence Nightiangel approach.